Effect of parachute and airbag in reducing safety risk posed by small UAS to people on the ground - Chengpeng Jiang; Henk Blom; Borrdephong Rattanagraikanakorn (Transportation Research Interdisciplinary Perspectives)
To reduce the safety risk posed by small Unmanned Aircraft System (UAS) to persons on the ground, one of the mitigating measures is to equip the UAS with an airbag in combination with a parachute, both of which are deployed in case of an uncontrolled descent. In literature, methods for the evaluation of the effect of a parachute alone have been developed. This paper develops a method to assess the safety risk for persons on the ground posed by a UAS that is both equipped with an airbag and a parachute. For the descent phase of the UAS to the ground, existing models are used. The novel part is the dynamical simulation of the effect on a human body of impact and interaction of a UAS with airbag. For the human impact simulation, use is made of Multi Body System (MBS) model for the UAS and the human; in combination with Finite Element (FE) model of the airbag. This method is applied for a specific parcel delivery UAS, of 15 kg weigh, for cases with and without airbag. The results obtained show that the combination of parachute and airbag can reduce the safety risk posed to people on the ground by more than one order in magnitude. Comparison with existing models for parachute alone, show that the novel method is much better in taking UAS design and material properties into account. The paper also shows that the dynamical simulation results obtained provide effective feedback to the further improvement of the airbag design.